Tensile properties, cell adhesion, and drug release behavior of chitosan-silver-gelatin nanohybrid films and scaffolds - Rana, V. K.; Kushwaha, Omkar S.; Singh, RajPal; Mishra, Satyendra; Ha, Chang-Sik (Macromolecular Research, 2010)
Drug-loaded nanohybrid films and porous scaffolds were prepared using chitosan, Ag nanoparticles and gelatin using a solution casting and freeze-drying method, respectively. Gelatin was used to incorporate the cell onto the surface of the scaffolds and the nanohybrid films. 1-[2-hydroxyethyl]-2-methyl-5-nitroimidazole) (Metronidazole (MTZ) was used as a model drug. The small percentage of Ag nanoparticles in the nanohybrid films and scaffolds produced significantly higher cell proliferation and levels of drug release. The tensile properties showed improvement in strength by Ag nanoparticles reinforcement at the expense of elongation.
Keywords: carcinogenic metronidazole; cell proliferation; chitosan-Ag-gelatin nanohybrids; drug release; nano-hybrids; scaffolds

Self photostabilizing UV-durable MWCNT/polymer nanocomposites - Lonkar, Sunil P.; Kushwaha, Omkar S.; Leuteritz, Andreas; Heinrich, Gert; Singh, R. P. (RSC Advances, 2012)
A potentially active hindered amine light stabilizer (HALS) was successfully anchored onto multiwalled carbon nanotubes (MWCNTs) and used as a light-stabilizing yet reinforcing multifunctional nanofiller to obtain UV-durable polymer nanocomposites. The influence of such light stabilizing MWCNTs on the photo-oxidation behaviour and structure-properties of polypropylene (PP) was studied. The composites were prepared by solution mixing of MWCNTs followed by melt compounding with polypropylene (PP). The resulting composite exhibits excellent UV-durability showing an almost 20 fold increase in the induction period of photo-oxidation. Moreover, the hydrophobic HALS was found to be compatibilizing enough to achieve homogeneous dispersion of exfoliated nanotubes into a polymer matrix. The rheological characterizations predict the formation of a percolated network structure. The obtained nanocomposites present markedly improved mechanical properties which underline the reinforcing ability of functionalized MWCNTs. Overall combination of HALS and MWCNTs offers an attractive route to combine multifunctionality into new hybrid UV-durable polymer nanocomposites. Such materials may possess great potential for outdoors high performance applications.

Preparation and characterization of self-photostabilizing UV-durable bionanocomposite membranes for outdoor applications - Kushwaha, Omkar S.; Avadhani, C. V.; Singh, R. P. (Carbohydrate Polymers, 2015)
Here, we report a durable and ultraviolet (UV) resistant nanocomposite membrane of chitosan (CS) with effective photostabilization ascribed to Zinc oxide (ZnO) nanoparticles. Zinc oxide nanoparticles were successfully dispersed in the solution of chitosan polymer. The nanocomposite films with the homogenous dispersion of ZnO nanoparticles in the chitosan matrix were obtained by solution casting method and the influence of ZnO nanoparticles as a photostabilizer was studied. The nanocomposite membranes were photoirradiated by polychromatic radiations with lambda > 300 nm using mercury vapour lamps in SEPAP instrument. The resulting nanocomposite material exhibited excellent UV-resistance in very low percentages of ZnO nanoparticles. The chitosan membranes showed fast degradation attributes than the nanocomposite membranes. ZnO nanoparticles effectively absorbed UV radiations, thus protecting polymer from radiation degradation. The neat and irradiated nanocomposites of chitosan and ZnO nanoparticles (CS/ZnO) were characterized by Fourier Transform Infrared Spectroscopy (FT-IR) spectroscopy for the chemical changes/degradation taking place. Chitosan nanocomposites were further characterized for tensile properties, contact angle measurements and surface morphology. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Bionanocomposite membrane; Chitosan; Contact angle measurement; Fourier transform infrared spectroscopy; Photostabilization; Zinc oxide nanoparticles

Fluorescent carbon nanodots for targeted in vitro cancer cell imaging - Aiyer, Sandhya; Prasad, Rajendra; Kumar, Manoj; Niryikar, K.; Jain, Bhanprakash; Kushwaha, Omkar S. (Applied Materials Today, 2016)
Carbon quantum dots (CQDs or C-dots, <= 10nm in size) are tiny carbon nanoparticles being envisaged in biosensing, bio-imaging and biomolecular/drug delivery. In the present investigation, green fluorescent carbon quantum/nano dots (GCQDs, similar to 3 nm in size) were synthesized through facile chemical slicing method. Further, folic acid (FA) functionalized GCQDs (GCQDs-FA) were obtained to enhance their targeting ability. FA is known to positively influence the binding potential and penetration into the cancer cells because of high abundance of folate receptors (FR) on various cancer cell membranes. We report high biocompatibility, photoluminescence stability and excellent in vitro cancer cell cytoplasm and nucleus targeting performance of GCQDs-FA on MCF-7 breast cancer cells. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Cancer cell bio-imaging; Carbon quantum/nano dots; Cell cytoplasm and nucleus targeting; Green fluorescence; Photoluminescence stability; Targeting ability

Kinetic promotion of methane hydrate formation by combining anionic and silicone surfactants: scalability promise of methane storage due to prevention of foam formation - Bhattacharjee, Gaurav; Barmecha, Vivek; Kushwaha, Omkar S.; Kumar, Rajnish (Journal of Chemical Thermodynamics, 2018)
Methane storage in its solid hydrate form has recently come up as a rather attractive and low risk option for large scale storage of the gas owing to its mild storage conditions, high gas retention capacity and benign (non-explosive) character. However, it has its fair share of limitations with the slow rate of hydrate formation being one of the most prominent. The addition of surfactants like Sodium dodecyl sulfate (SDS) to the hydrate forming system significantly speeds up the process of methane hydrate formation but the large amount of foam generated by these surfactants during the process of hydrate formation and dissociation stands as a major roadblock towards the scaling up of the technology. In the current work, a small amount of a silicon based surfactant has been proposed to be used as antifoam in conjunction with an anionic surfactant SDS to eliminate the foam generation while at the same time promote the kinetics of methane hydrate formation. The idea is simple, cost effective and can be a potential game-changer in the quest to develop a commercially scalable hydrate based methane storage technology. (C) 2017 Elsevier Ltd.
Keywords: Antifoam; Gas hydrate; kinetics; Methane storage; scale-up; Silicone surfactant

Fluorescent carbon nanodots for targeted in vitro cancer cell imaging (vol 4, pg 71, 2016) - Aiyer, Sandhya; Prasad, Rajendra; Kumar, Manoj; Nirvikar, K.; Jain, Bhanprakash; Kushwaha, Omkar S. (Applied Materials Today, 2019)

Methane recovery from marine gas hydrates: a bench scale study in presence of low dosage benign additives - Bhattacharjee, Gaurav; Choudhary, Nilesh; Barmecha, Vivek; Kushwaha, Omkar S.; Pande, Nawal K.; Chugh, Parivesh; Roy, Sudip; Kumar, Rajnish (Applied Energy, 2019)
De-pressurization is one approach which has been found to be economically feasible for methane recovery from marine hydrates. Hydrate dissociation being an endothermic process suggests that de-pressurization alone would not be sufficient and some additional stimulation would be required for sustained production from one such reservoir. Thermal stimulation may overcome the challenge posed by the endothermic dissociation process; however, economically it may not be ideal. A possible way out is to use thermal stimulation, but at relatively low temperatures as compared to conventional practice. This would be economical and can be accomplished in the presence of small doses of additives mixed in with the water stream used for thermal stimulation. In the present study, a number of benign additives were identified which when used in low concentrations enhance the kinetics of methane hydrate dissociation compared to pure water. Additives were first shortlisted from a wide potential pool using quantum mechanical calculations. These additives were later tested for their efficacy in stirred tank reactor to quickly identify the best additives for the job and few selected additives were then studied in a larger bench scale setup (fixed bed configuration) where they were injected in the form of an additive-water stream to dissociate already formed hydrates. Factors such as toxicity of the additive, fluidity of additive-water stream, foam formation on mixing of additive with water, etc. were also taken into account. An energy and efficiency analysis revealed that reported additives enhance the energy ratio and thermal efficiency of the process as compared to pure water stimulation.
Keywords: Bench scale; kinetics; Marine hydrate; methane hydrate; Methane recovery; Natural gas hydrate; Process